COMMUNICATIVE ACTIONS OF THE INDONESIAN GOVERNMENT DURING THE COVID-19 PANDEMIC IN ONLINE MEDIA - Irfan Fauzi; Andi Mirza Ronda; Suraya Mansur; Anita Rosana (International Journal of Social Science, 2023)
This study focuses on the government’s communicative actions in public sphere during the 2020 Covid-19 pandemic. The government’s steps have seen to be experiencing inconsistency, ambiguity, and counter productiveness in handling the Covid-19 pandemic issue. The material objects in this study are government statements quoted by three online mass media, namely kompas.com, tribunnews.com, and detik.com, which were published from March to May 2020. There were twelve selected media articles from these media. The text was analyzed using critical discourse analysis. This research uses a qualitative approach with a critical paradigm. The research data is processed using Habermas’ communicative action theory where the validity of a communication is tested through 4 validity claims, such as truth, sincerity, comprehensibility, and legitimacy. The results of the study explained that from 12 news containing 31 government statements, found 10 confusing statements, 6 erroneous statements, 7 false impressions and 8 illegitimacy and inaccuracies. This shows an indication of the government’s inability to act communicatively, especially in the aspect of comprehensiility claims that lead to information distortion. The government statements use a lot of jargon and terms that are not well defined, lead to misinformation